2020
DOI: 10.34133/2020/3074916
|View full text |Cite
|
Sign up to set email alerts
|

RhizoVision Crown: An Integrated Hardware and Software Platform for Root Crown Phenotyping

Abstract: Root crown phenotyping measures the top portion of crop root systems and can be used for marker-assisted breeding, genetic mapping, and understanding how roots influence soil resource acquisition. Several imaging protocols and image analysis programs exist, but they are not optimized for high-throughput, repeatable, and robust root crown phenotyping. The RhizoVision Crown platform integrates an imaging unit, image capture software, and image analysis software that are optimized for reliable extraction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 55 publications
0
68
0
1
Order By: Relevance
“…The challenge now is to develop new and improved analytical tools, capable of transforming this wealth of data into valuable knowledge [ 15 ]. This is a rapidly evolving field, and numerous software and pipelines to automatize phenotype collection are already available [ 18 – 22 ]. Many of these tools focus on the analysis of root images and, as far as we know, require more user intervention than we propose, making it impractical to analyze hundreds of images.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge now is to develop new and improved analytical tools, capable of transforming this wealth of data into valuable knowledge [ 15 ]. This is a rapidly evolving field, and numerous software and pipelines to automatize phenotype collection are already available [ 18 – 22 ]. Many of these tools focus on the analysis of root images and, as far as we know, require more user intervention than we propose, making it impractical to analyze hundreds of images.…”
Section: Introductionmentioning
confidence: 99%
“…This study relied on manual measurements and scoring of root traits, an approach that has been used for a variety of crops (Trachsel et al, 2011 ; Burridge et al, 2016 ). With the advent of image-based methods, higher throughput and possibly greater precision of trait measurement due to less time spent evaluating traits and human bias or error (Bucksch et al, 2014 ; Colombi et al, 2015 ; Seethepalli et al, 2020 ) will allow more ambitious studies to expand on the findings reported here. Alleviating the phenotyping bottleneck for roots through the utilization of new technologies like imaging and image analysis for root traits is expected to enhance future genetic and physiological studies.…”
Section: Discussionmentioning
confidence: 90%
“…Many algorithms and software packages have been devised to extract complex features and traits from still images [39]. Programs such as DIRT [42,43], archiDART [44], EZ-Root-VIS [45], GiA Roots [46], WinRHIZO (Regent Instrument Inc., Ville de QuĂ©bec, QC Canada), and RhizoVision [47] provide a means to measure of a variety of traits of interest; such as root lengths, diameter classes, volumes, and surface areas of individual roots or entire root systems of many species, for example, Zea mays [48].…”
Section: Imaging Methods For Root Systemsmentioning
confidence: 99%